2021
DOI: 10.1038/s41467-021-23022-1
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration of lipid reproduction by emergence of microscopic motion

Abstract: Self-reproducing molecules abound in nature where they support growth and motion of living systems. In artificial settings, chemical reactions can also show complex kinetics of reproduction, however integrating self-reproducing molecules into larger chemical systems remains a challenge towards achieving higher order functionality. Here, we show that self-reproducing lipids can initiate, sustain and accelerate the movement of octanol droplets in water. Reciprocally, the chemotactic movement of the octanol dropl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 42 publications
0
27
0
Order By: Relevance
“…Controlling the chemistry of such reaction-driven Marangoni flows becomes then an interesting approach to achieve complex behavior at air-water interfaces and within organic droplets. [44][45][46] Such insight is also useful to develop applications where Marangoni flows are used for propulsion, [47,48] self-assembly direction [49][50][51] or to design systems with Marangoni-based feedback mechanisms. [52]…”
Section: Discussionmentioning
confidence: 99%
“…Controlling the chemistry of such reaction-driven Marangoni flows becomes then an interesting approach to achieve complex behavior at air-water interfaces and within organic droplets. [44][45][46] Such insight is also useful to develop applications where Marangoni flows are used for propulsion, [47,48] self-assembly direction [49][50][51] or to design systems with Marangoni-based feedback mechanisms. [52]…”
Section: Discussionmentioning
confidence: 99%
“…We could observe that Marangoni convection (blue arrow) occurred inside the droplet because ejection points were transported along the interface. Therefore, we inferred that this convection, which has been identified as the primary driving force in many selfpropelled droplet systems, was the cause of the self-propulsion of the droplet in this system [40][41][42][43][44][45][46]. In general, Marangoni convection occurs when the interfacial tension γ at the droplet interface becomes unbalanced.…”
Section: Self-propelled Motion Of a Single Dropletmentioning
confidence: 99%
“…In this phenomenon, surfactant molecules first enter the lipid membrane with an increasing surfactant concentration, and aggregates of the surfactant and lipid molecules are formed as surfactant concentration is increased further. Furthermore, another study showed that solubilization, namely micellization of surfactants with oil, and ejection of solubilized emulsions proceed when the concentration of the surfactant at the droplet interface exceeds a threshold value [46]. Therefore, we infer that, in this study, TSA + is first inserted into the self-assembled DMPC monolayer surrounding the droplet, and aggregated emulsions are formed and ejected them owing to the solubilization promoted by the micellization among TSA + , DMPC, and nitrobenzene oil when the concentration of the inserted TSA + exceeds a threshold value.…”
Section: Self-propelled Motion Of a Single Dropletmentioning
confidence: 99%
“…This imbalance results in an internal Marangoni flow, which propels the droplet towards the side with the highest surfactant concentration. 25,26,28 Alternatively, self-organizing elements can interact via capillary effects, which involve the deformation of a liquid interface caused by objects in contact with it. 29 Capillary forces have been demonstrated to deform elastic microstructures, 30,31 even causing them to collapse into hierarchical assemblies.…”
Section: Introductionmentioning
confidence: 99%